2006
DOI: 10.1002/jcc.20503
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio QM/MM dynamics of H3O+ in water

Abstract: A molecular dynamics (MD) simulation based on a combined ab initio quantum mechanics/molecular mechanics (QM/MM) method has been performed to investigate the solvation structure and dynamics of H3O+ in water. The QM region is a sphere around the central H3O+ ion, and contains about 6-8 water molecules. It is treated at the Hartree-Fock (HF) level, while the rest of the system is described by means of classical pair potentials. The Eigen complex (H9O4+) is found to be the most prevalent species in the aqueous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 65 publications
(64 reference statements)
2
37
0
Order By: Relevance
“…[44] that a complete understanding of the water exchange mechanisms requires information on both hydration structures and dynamics, which are closely related to the interactions and momentum transfer between water molecules in the first and second hydration shells. The influence of water molecules in the second hydration shell was also illustrated in our previous work on [NH 4 + ] aq [73] and [H 3 O + ] aq [74]. Especially in the case of [H 3 O + ] aq [74], it was shown that water molecules in the second hydration shell could help promote the proton transfer from H 3 O + to H 2 O, through the formation of the Zundel complex (H 5 O 2 + ).…”
Section: [Li + /Ala] Aqmentioning
confidence: 80%
See 1 more Smart Citation
“…[44] that a complete understanding of the water exchange mechanisms requires information on both hydration structures and dynamics, which are closely related to the interactions and momentum transfer between water molecules in the first and second hydration shells. The influence of water molecules in the second hydration shell was also illustrated in our previous work on [NH 4 + ] aq [73] and [H 3 O + ] aq [74]. Especially in the case of [H 3 O + ] aq [74], it was shown that water molecules in the second hydration shell could help promote the proton transfer from H 3 O + to H 2 O, through the formation of the Zundel complex (H 5 O 2 + ).…”
Section: [Li + /Ala] Aqmentioning
confidence: 80%
“…The influence of water molecules in the second hydration shell was also illustrated in our previous work on [NH 4 + ] aq [73] and [H 3 O + ] aq [74]. Especially in the case of [H 3 O + ] aq [74], it was shown that water molecules in the second hydration shell could help promote the proton transfer from H 3 O + to H 2 O, through the formation of the Zundel complex (H 5 O 2 + ). The MD trajectory in Fig.…”
Section: [Li + /Ala] Aqmentioning
confidence: 80%
“…While many investigations are focused on the quality and robustness of the employed theoretical methods [48, 604-606, 609, 614, 616-618, 621], lots of studies on the solvent shell structure around common ions [607-610, 612-617, 619, 624-628] or pure solvents [646] have also been published. Nevertheless, both methods are much better suited to describe experimental results than a description based on pure classical mechanics [608,610,613,622,628]. Both QM methods are known to have severe deficiencies, but the use of more sophisticated methods is, due to their enormous computational demands, limited to small reference systems and benchmark calculations.…”
Section: Structures In Solvents Due To Ionsmentioning
confidence: 99%
“…Despite these limitations, ab initio simulations have provided important atomistic insights into the transfer mechanism of hydrated protons, which can be used for developing and parameterizing more approximate approaches. In an effort to gain efficiency, while preserving the detailed description of the excess proton, approaches based on semiempirical methods and hybrid quantum/classical protocols have been proposed …”
Section: Introductionmentioning
confidence: 99%
“…In an effort to gain efficiency, while preserving the detailed description of the excess proton, approaches based on semiempirical methods [3,4] and hybrid quantum/classical protocols have been proposed. [5] More toward a molecular description, but still capable of explicit proton transfer, are empirical valence bond (EVB) [6][7][8][9][10][11] and reactive force field [12][13][14][15][16] approaches. Typically, a classical MD simulation is performed, during which proton transfer is evaluated in an effective potential energy landscape extracted from ab initio calculations of model transfer events.…”
Section: Introductionmentioning
confidence: 99%